Drought management for California almonds. Issue 2 (24th May 2016) - Doll, David; Shackel, Kenneth
Abstract : Almond trees are tolerant to drought conditions and respond to water availability with increasing yields. Research has shown that trees are able to survive on as little as 7.6 inches of water, but they produce maximally with 54 to 58 inches in many areas of California. Minimizing water stress increases growth and yield due to increased rates of photosynthesis and respiration. Earn 2 CEUs in Soil & Water Management by reading this article and taking the quiz at www.certifiedcropadviser.org/certifications/self‐study/765 .